2000
DOI: 10.1177/107484070000600206
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Parent-Adolescent Communication and Safer Sex Behaviors in College Students

Abstract: An increased incidence of HIV infection in adolescents has led researchers to examine factors that influence young people’s sexual behaviors. One of these factors is parent-adolescent communication about sexuality. In this study, two measurements of this communication were developed and tested through a mailed survey instrument methodology, with a sample of 732 college students. The instruments were found to be psychometrically sound. An exploration of the associations between selected demographic variables, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 19 publications
4
57
0
2
Order By: Relevance
“…Although the overall influence of maternal attachment on adolescent boys is expected to be positive, American studies among college students have indicated that mothers do not often talk to their sons about sexuality, thus turning their general caring support for their sons' opinions and actions more open for interpretation (Epstein and Ward 2008;Lehr et al 2000). Additionally, research in the U.K. has pointed out that maternal attachment may increase boys' sexual self esteem (Taris and Semin 1998).…”
Section: Maternal Attachment and Adolescent Sexual And Gender Stereotmentioning
confidence: 93%
“…Although the overall influence of maternal attachment on adolescent boys is expected to be positive, American studies among college students have indicated that mothers do not often talk to their sons about sexuality, thus turning their general caring support for their sons' opinions and actions more open for interpretation (Epstein and Ward 2008;Lehr et al 2000). Additionally, research in the U.K. has pointed out that maternal attachment may increase boys' sexual self esteem (Taris and Semin 1998).…”
Section: Maternal Attachment and Adolescent Sexual And Gender Stereotmentioning
confidence: 93%
“…A substantial body of scholarship has demonstrated the importance of family to adolescent sexual and romantic relationships (Bersamin et al 2008;Hutchinson and Cederbaum 2011;Lehr et al 2000;Markham et al 2010). Longmore et al (2009: 1) study of adolescent sexual initiation argues that parents are a ''countervailing'' force to peers in adolescence.…”
Section: Literature Family Influences In Adolescence and Emerging Adumentioning
confidence: 98%
“…For example, a number of studies showed that parent-child communication about sexual issues is associated with delayed onset of sexual intercourse (e.g., Aspy et al, 2007;Lehr, DiIorio, Dudley, & Lipana, 2000), increased contraceptive use (including condom use), and fewer sexual partners (e.g., Holtzman & Rubinson, 1995;Pick & Palos, 1995).…”
Section: Theoretical Rationalementioning
confidence: 99%